The Effect of Work Role Conformity and Role Conflict on the Performance of Administrative Employees at State Vocational Schools in Buleleng Regency - Putu Ermayanti; Putu Indah Rahmawati; I Nengah Suarmanayasa (Universitas Pendidikan Ganesha, 2022)
The problem that often arises is role conflict. The existence of role conflict in an agency certainly dramatically affects the performance of its employees. Role conflicts can occur due to differences in commitment, inappropriate communication language, character, ethics, and individual behavior in social relationships and job competition. The purpose of this study is to analyze the effect of work role suitability and role conflict on the performance of administrative employees at State Vocational Schools in Buleleng Regency. This type of research is ex-post facto quantitative research. The subjects in this study were administrative employees, while the object of this study was the suitability of work roles, role conflicts, and performance of administrative employees. The population in this study were all administrative employees totaling 195 respondents with the Slovin formula calculation formula. The data collection technique used a questionnaire method which was filled in via Google Forms with a Proportional Random Sampling system. The data analysis technique used Path Analysis Test. The results of the study show: first, work role congruence and role conflict have a positive and significant direct effect on employee performance variables. Second, the suitability of work roles to administrative role conflicts shows that the suitability of work roles has a positive and significant direct effect on role conflicts. Third, the suitability of work roles on the performance of administrative employees shows that Role Conflict has a positive and significant direct effect on performance. Fourth, role conflict on administrative employee performance because the Role Conflict variable has a positive and significant direct effect on employee performance.